Analisis Pengaruh Karakteristik Bank, Faktor Makroekonomi terhadap Pembiayaan Sektor UMKM pada Perbankan Syariah di Indonesia - Lestari, Lutfi Bangun; Afandi, Akhsyim (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2020)
MSMEs have an important role in national economic development, but capital is still the main problem faced in developing MSMEs. Islamic banking has a main function, one of which is channeling financing. However, the trend in financing the MSME sector always fluctuates from year to year and tends to decline. This study aims to analyze the effect of bank characteristics and macroeconomic factors on the financing of the MSME sector in Islamic banking in Indonesia. This study uses time series data which is monthly data on aggregate financial statements of Islamic Commercial Banks and Sharia Business Units in Indonesia. The analysis method used in this research is Autoregressive Distributed Lag (ARDL). The results showed that the variables that affect the financing of the BUS MSME sector in the short term are return on assets (ROA) and the interest rate (BI_Rate). Whereas in the long term, the variables that affect the financing of the BUS MSME sector are the bank office network (JKB) and inflation. While variable third party funds (DPK), non-performance financing (NPF), exchange rates, equivalent rate of financing (ERP) both in the short term and long term have no effect on the financing of the BUS MSME sector. Then the variables that affect UUS MSME sector financing in the short term are the bank office network (JKB), return on assets (ROA) and the interest rate (BI_Rate). Whereas in the long term, the variable that affects UUS MSME sector financing is the bank office network (JKB). Meanwhile, the variable of third party funds (DPK), non-performance financing (NPF), exchange rate, equivalent rate of financing (ERP) both in the short and long term had no effect on the financing of the UUS MSME sector.Â